Electrokinetics at liquid-liquid interfaces: Physical models and transport mechanisms - Huang, Yunfan; Wang, Moran (Advances in colloid and interface science, 2025)
The electrification effects and electrokinetic flow phenomena at immiscible liquid-liquid interfaces have been a subject of scientific inquiry for over a century. Unlike solid-liquid interfaces, liquid-liquid interfaces exhibit not only multiphysical and cross-scale characteristics but also diffuse soft properties, including finite thickness, fluidity, ion adsorbability, and permeability, which introduces diverse interfacial charging mechanisms and conductive dielectric properties, imparting unique characteristics to electrokinetic multiphase flow systems. Electrokinetic multiphase hydrodynamics (EKmHD), grounded in electrochemistry and colloid and interface science, has experienced renewed interest in recent years. This is particularly evident in systems such as the interface between two immiscible electrolyte solutions (ITIES) in electrochemistry, self-propelling droplets in physicochemical hydrodynamics, and digital microfluidics in electromechanics. The multiphase diffuse soft nature of charged liquid-liquid interfaces introduces novel physical scales and theoretical dimensions, positioning EKmHD as a potential foundation for a new interdisciplinary field rather than merely a cross-disciplinary area. This review highlights the need for an integrated research approach that combines interfacial charging mechanisms with electrokinetic flows, alongside a cross-scale modeling framework for interfacial multiphysical transport. It systematically organizes the characteristics of liquid-liquid interfaces from the perspectives of charging mechanisms and electrokinetic behaviors, with particular emphasis on spontaneous partition- and adsorption-induced charging at the interface, and the strong coupling between multiphase diffuse soft interface flow and ion transport. Furthermore, the paper comprehensively summarizes the transport mechanisms of electrokinetic multiphase flows concerning interfacial ion transport and fluid flow, while refining the corresponding dominant dimensionless parameters. Additionally, it systematically consolidates current understanding of typical electrokinetic multiphase flow scenarios, with special focus on potential future research directions. These include the electrokinetic double-sided coupling effects in ITIES systems, solidification and nonlinear effects in droplet/bubble electrophoresis, the validity of the leaky dielectric model, electrokinetic instabilities of jets and ion-selective soft interfaces, and the active and passive control of two-phase electrokinetic wetting dynamics and displacement. [Display omitted] •A comprehensive review of progress on the modeling and mechanism of electrokinetic multiphase hydrodynamics (EKmHD) at liquid-liquid interfaces.•A new cross-scale paradigm has been presented for the liquid-liquid EKmHD with complex multiphase diffuse interfaces considering inherent ion transfer mechanisms.•Dimensionless groups systematize interfacial ion transport and fluid flow, enabling mechanism analysis in typical scenarios of charged droplet and interface dynamics.